Gambaran Pengetahuan Ibu Hamil Trimester III Tentang Persalinan Kala I Memanjang Di Klinik Helen Tarigan Di Kota Medan Tahun 2021 - Nurhayani Purba (Healthcaring: Jurnal Ilmiah Kesehatan, 2022)
First stage of labor is said to be prolonged if it has lasted more than 24 hours in primi and 18 hours in multistage I prolonged latent phase, the uterus tends to be in a hypertonic state, this can result in inadequate contractions and only mild (less than 15 mm Hg on the monitor screen), therefore uterine contractions are ineffective. This study aims to obtain a description of the knowledge of third trimester pregnant women about the first stage of lengthening at the Helen Tarigan Clinic in 2021.